2004
DOI: 10.1097/01.ijg.0000141366.45974.3a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Indentation Ultrasound Biomicroscopy Gonioscopy in Relative Pupillary Block, Peripheral Anterior Synechia, and Plateau Iris Configuration

Abstract: Indentation UBM gonioscopy is a very useful method for observing the angle and diagnosis of RPB, PAS, and PIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…It can also confirm the double hump sign which is normally seen with gonioscopy by use of an indentation UBM, a special technique that imposes mild pressure on peripheral cornea with the skirt of eyecup. 13 Matsunaga K et al 14 studied Indentation UBM gonioscopy. They found that the angle of all examined eyes was significantly widened with indentation.…”
Section: Determining the Mechanism Of Primary Glaucomamentioning
confidence: 99%
“…It can also confirm the double hump sign which is normally seen with gonioscopy by use of an indentation UBM, a special technique that imposes mild pressure on peripheral cornea with the skirt of eyecup. 13 Matsunaga K et al 14 studied Indentation UBM gonioscopy. They found that the angle of all examined eyes was significantly widened with indentation.…”
Section: Determining the Mechanism Of Primary Glaucomamentioning
confidence: 99%
“…The advent of UBM has enabled high-resolution images of the angle region and anterior chamber, and thus has been instrumental in differentiating the cause of angle-closure 11 14 – 17. UBM uses high-frequency ultrasound (50–100 MHz) to produce images of the anterior segment at a high resolution (20–50 um)10 14 that allows structural details of the angle and the ciliary body to be microscopically visualized 10 15 18.…”
Section: Discussionmentioning
confidence: 99%
“…UBM uses high-frequency ultrasound (50–100 MHz) to produce images of the anterior segment at a high resolution (20–50 um)10 14 that allows structural details of the angle and the ciliary body to be microscopically visualized 10 15 18. In addition to confirming the diagnosis of PPI and PI, UBM may be very helpful in ruling out other posterior peripheral iris push mechanisms such as an anterior uveal effusion and a ciliary body tumour—for example, diffuse ciliary body melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…72 Following this work, Matsunaga et al described the use of a special UBM eyecup that allowed simultaneous corneal compression with UBM observation of the angle configuration before and after compression. 73 This eyecup allowed a differentiation between appositional angle closure and synechial closure. Carillo demonstrated the usefulness of UBM to diagnose obstruction of an Ahmed valve by the iris (Figure 11).…”
Section: Angle Recessionmentioning
confidence: 99%